Novel Mega Best-Seller Karya Luluk HF Mariposa dalam Kajian Resepsi Sastra - Tania Intan; Muhamad Adji (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
This study discusses the reception of readers of the mega best-seller novel entitled Mariposa by Luluk HF. The purpose of this study is to (1) describe the reader's responses, (2) describe the horizon of readers' expectations, and (3) describe the factors that cause differences in responses and the horizon of expectations of readers of Mariposa's novel. The method applied is descriptive qualitative. This study uses a reception aesthetic approach that seeks to find consistent reception patterns as a reflection of the way the reader responds to the text. The research data consisted of texts containing the responses of twenty respondents from the data source in the form of the Goodreads reader site. The research results obtained are as follows. First, not all readers respond positively to the intrinsic elements of the novel, especially the characterization of the female protagonist who is considered to show aggressive behavior with a love motive. Second, most of the horizons of readers' expectations do not match the reality in Mariposa. Readings are generally motivated by curiosity because of the hyperbolic labeling of the novel, recommendations from friends, and the discourse of filming the novel. Third, the factors that cause the difference or suitability of the horizon of readers' expectations for the Mariposa novel are knowledge of literature, knowledge of life, and experience of reading literary works.